ANALISIS KESENJANGAN PERAN WARGA NEGARA KAMPUS ANTARA KESADARAN ISU, MINIMNYA SALURAN FORMAL, DAN IKLIM KETAKUTAN DI KALANGAN MAHASISWA - Danish Ayman Pratama; Muhammad Fitran Ramadhan; Fahrial Al Akbar Warsito Putra; Muhammad Darul Rizqullah; Muhammad Wira Al Fikri (Universitas Nias Raya, 2025)
This study analyzes the gap in formal opinion participation among Telkom University students, despite their high awareness of campus issues. Using a descriptive qualitative approach, general students and the student press were interviewed to examine the factors inhibiting opinion participation. The results indicate that low formal participation is caused by two main factors: the Channel Awareness Factor (massive ignorance about opinion platforms, including anonymity features, in campus media) and the Freedom of Speech Climate Factor (the existence of a chilling effect or climate of fear validated by the intervention experience experienced by the student press). The conclusion highlights that the role of